Self-medication of antibiotics: investigating practice among university students at the Malaysian National Defence University - Haque, Mainul; A Rahman, Nor Azlina; McKimm, Judy; Kibria, Golam Mohammad; Majumder, Md Anwarul Azim; Haque, Seraj Zohurul; Islam, Md Zakirul; Abdullah, Shahidah Leong; Mohammad Daher, Aqil; Zulkifli, Zainal; Rahman, Sayeeda; Kabir, Russell; et al. (Dove Medical Press Ltd., 2019)
Background: Self-medication of drugs to alleviate symptoms is a common global behavior, helping relieve burdens on health services, but many drugs eg, antibiotics are prescription-only. Self-medication of antibiotics (SMA) is an irrational use of drugs, contributing to microbial resistance increasing health care costs and higher mortality and morbidity. This study aimed to assess SMA among university students. Methods: This was a cross-sectional study conducted among medical and non-medical students of the National Defence University of Malaysia. A validated instrument was used to gather data. Ethics approval was obtained. Random and universal sampling was adopted, and SPSS 21 was used for data analysis. Results: A total of 649 students participated in the study: 48.5% male and 51.5% female, 39.3% reported self-medicating with antibiotics. Penicillin, doxycycline, clarithromycin were the antibiotics most used with the majority reporting no adverse drug reactions. Cost savings and convenience were the principal reasons for SMA which were mainly obtained from local retail pharmacies. Despite medical students (particularly the more senior) having better knowledge of antibiotic use than non-medical students, 89% of all research participants responded that practicing SMA was a good/acceptable practice. Conclusion: SMA is common amongst Malaysian students and, despite understanding why SMA is unwise, even medical students self-medicate.